Estimation of hydraulic parameters using electrical resistivity tomography (ERT) and empirical laws in a semi-confined aquifer - Perdomo, Santiago (2018)
The estimation of hydraulic parameters is critical for the rational use of water resources and the development of reliable hydrogeological models. However, the cost of such estimation can be very high and the data are limited to the area near the pumping well. For this reason, complementary methods for estimating hydraulic conductivity and transmissivity have become increasingly important in recent years, such as the adjustment of empirical relationships between geoelectrical and hydraulic parameters. In this paper, two linear relationships were tested, combining resistivity measurements from well logging profiles and hydraulic conductivity values from pumping test data, in a semi-confined fluvial aquifer in the province of Buenos Aires, Argentina. Furthermore, these relationships were used to obtain two-dimensional (2D) hydraulic conductivity and transmissivity sections from electrical resistivity tomography using a high-definition electrode array. Predicted values were compared with traditional pumping test in a near well showing very good agreement with both methods. Results showed that it would be possible to quantify the 2D variation of hydraulic parameters in aquifers and to identify high- or low-productivity areas. By knowing this information in advance, it is possible to reduce the number of failures or unexpected results when drilling a well. These 2D sections also provide additional information about hydraulic parameters and their lateral variability, and can improve hydrogeological models without drilling new wells.